Robot-assisted surgery in complex treatment of the pulmonary tuberculosis - Yablonskii, Piotr (J Vis Surg, 2017)
Surgery of pulmonary tuberculosis associated with open thoracotomy due to dense pleural and vascular adhesions. These reasons limited the use of video-assisted thoracoscopic surgery (VATS) in these cases. Robotic surgical system aimed to performing successfully minimally invasive operations for pulmonary tuberculosis. This paper showed 3-year experience of one chest center in this area. The results of this work are recommendations that facilitate the implementation of robot-assisted lung resection in complex treatment of pulmonary tuberculosis.